WORKING CAPITAL MANAGEMENT VS. PROFITABILITY OF MILK PROCESSING COMPANIES - Zbigniew GOŁAŚ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper analyzes the relationships between the efficiency of working capital management and the return on assets of milk processing companies. Working capital management was assessed for efficiency based on the Days Sales of Inventory (DSI), Days Sales Outstanding (DSO), Days Payable Outstanding (DPO) and the Cash Conversion Cycle (CCC). The study was based on micro-data for dairy companies from 2007–2016 retrieved from the EMIS database. Based on panel regression models, it was concluded that an improvement in working capital management has a positive effect on the return on assets. The parameters of the models clearly showed that an increase in the DSI, DSO, DPO and CCC resulted for the dairy companies in a reduction in the return on operating assets